Impact of some agricultural policy measures on economic position of dairy producers - Zoran Grgić; Ramona Franić; Teo Vujčić (Mljekarstvo)
In this paper we used data from survey of production and economicresults of selected family farms and data from LURA d.d. (joint-stockcompany), to estimate economic position of dairy producers within the period 2000-2002. Basic elements used for the estimation of the economic position of dairy production were realized revenues, income and profit per dairy cow and per household (farm). The influence of some more important measures of agricultural state support, such as subsidies for milk and registered heads, as well as for fodder growing, on farmers' income, was additionally analysed. Furthermore, the influences of favourable credit lines for the farm enlargement, purchase of dairy cows, dairy equipment and building the farm capacities were analysed as well. With regards to current structure of dairy producers in Croatia, we investigated family farms with different levels of annual production (from 10 thousand to 50 thousand lit. of milk). Great deviations of revenues, income and profit in milk production per dairy cow in investigated farms suggest that there are great un-used financial effects from subsidies in dairy production for the majority of rather small producers.